Polypropylene microfibers via solution electrospinning under ambient conditions. Issue 45 (5th July 2019) - Acik, Gokhan; Altinkok, Cagatay
ABSTRACT: Uniform beadless fibers of chlorinated polypropylene (PP‐Cl) are prepared by electrospinning of PP‐Cl solutions in tetrahydrofuran at different concentrations, feed rates, applied voltages, and tip‐to‐collector distances (TCDs) under ambient conditions for the first time. Average fiber diameter and morphology of the electrospun PP‐Cl fibers are determined by scanning electron microscopy. On the other hand, the wettability of the fibers is examined by water contact angle (WCA) measurements. Furthermore, thermal behavior of fibers is investigated by differential scanning calorimetry and thermogravimetric analyses, respectively. Obtained results show that the higher concentrations and feed rates of polymer solutions not only enhance the average diameter of the electrospun fibers ranging from 2.2 ± 0.5 to 2.8 ± 0.3 μm but improve the hydrophobicity of the fiber surfaces from 128° ± 1.1 to 141° ± 1.0 as well. On the other hand, when applied voltage is increased or TCD is decreased, diameters of achieved fibers are enhanced. It is suggested that PP‐Cl is an useful material for solution electrospinning process at under ambient conditions, exhibiting great scientific merit and good industrial expectation in the potential PP applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48199. Abstract : Chlorinated polypropylene (PP‐Cl)‐based microfibers are synthesized via simple solution electrospinning process under ambient conditions for the first time. Moreover, it has been reported the effect of solution concentration, feed rate, applied voltage, and tip‐to‐collector distance on the fabrication of electrospun PP‐Cl microfibers. Their morphological, wetting, and thermal properties are investigated by scanning electron microscope, water contact angle, differential scanning calorimetry, and thermogravimetric analyses.